Curative Effects of Fuzheng Huayu on Liver Fibrosis and Cirrhosis: A Meta-Analysis. (28th June 2015) - Dong, Shu; Chen, Qi-Long; Su, Shi-Bing
Abstract : The Fuzheng Huayu (FZHY) formula is being used in antiliver fibrosis treatment in China. For systemic evaluation of the curative effects of FZHY on liver fibrosis and cirrhosis progress, a total of 1392 subjects (714 cases and 678 controls) were found to be eligible for meta-analysis in this study. Standard mean differences (SMDs) with 95% confidence interval (CI) were calculated for changes between FZHY groups and controls by employing fixed effects or random effects model. In the overall analysis, alanine transaminase (ALT) (P = 0.003, SMD = −0.87, 95% CI: −1.46 to −0.29), total bilirubin (TBil) (P = 0.001, SMD = −1.30, 95% CI: −2.10 to −0.50), hyaluronic acid (HA) (P = 0.000, SMD = −0.94, 95% CI: −1.30 to −0.58), laminin (LN) (P = 0.000, SMD = −0.80, 95% CI: −1.20 to −0.41), type III procollagen (PC-III) (P = 0.000, SMD = −1.27, 95% CI: −1.93 to −0.60), and type IV procollagen (IV-C) (P = 0.000, SMD = −0.78, 95% CI: −1.05 to −0.51) were decreased after FZHY treatment; however, albumin (ALB) was increased (P = 0.037, SMD = 1.10, 95% CI: 0.07 to 2.12) significantly. Furthermore, the Child-Pugh score was reduced significantly and the life quality was improved after FZHY treatment in cirrhosis patients. The results of this meta-analysis indicated that FZHY effectively improves the liver function, alleviates hepatic fibrosis, decreases Child-Pugh score, and relieves TCM symptoms caused by liver dysfunction, indicating that FZHY may contribute to the alleviation of liver fibrosis and cirrhosis.